2019
DOI: 10.3892/etm.2019.7808
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of histone modification‑associated genes on differential gene expression and prognosis in gastric cancer

Abstract: Accumulating evidence suggests that the epigenetic alterations caused by histone modifications have important roles in the genesis of gastric cancer (GC), particularly the well-studied acetylation and methylation modifications. In the present study, a Bioinformatics analysis of the expression of histone modification-associated genes in GC and normal tissues was performed by using datasets from Oncomine, the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA). The clinical data of GC patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Hence, during dynamic packaging, maintaining stable and ordered chromatin is vital to ensure normal cellular homeostasis. Factors influencing the number of chromatin-associated cellular events, including transcription, warped histones, and DNA, are subject to covalent posttranslational modifications (50). In the present study, a comparative analysis of histone modifications in tumor and normal tissues was conducted, which revealed that the DEGs were primarily regulated by H3K27me3 in several cancer cell lines.…”
Section: Discussionmentioning
confidence: 85%
“…Hence, during dynamic packaging, maintaining stable and ordered chromatin is vital to ensure normal cellular homeostasis. Factors influencing the number of chromatin-associated cellular events, including transcription, warped histones, and DNA, are subject to covalent posttranslational modifications (50). In the present study, a comparative analysis of histone modifications in tumor and normal tissues was conducted, which revealed that the DEGs were primarily regulated by H3K27me3 in several cancer cell lines.…”
Section: Discussionmentioning
confidence: 85%
“…However, several studies noticed that the PRDM16 gene was hypermethylated and downregulated in lung cancer ( Table 4 ) [ 48 ], [ 49 ], [ 50 ]. The CLASP2 gene showed differential expression levels in lung, gastric, and bladder cancers [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Promotor hypermethylation and downregulated expression of the PRDM16 gene was observed in lung cancer [ 49 ]. In gastric cancer, decreased PRDM16 expression was associated with an unfavorable prognosis [ 50 ]. Methylation status of the CLASP2 gene has not been studied; however, the gene upregulation was detected in bladder cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of AS events on the prognosis of patients was analyzed, and a survival prediction model was constructed ( Zhang et al, 2019 ). Because the driving factors of tumorigenesis and development are generally differentially expressed in tumors and normal tissues ( Meng et al, 2019 ), this article is limited because the data of adjacent normal tissues were not included in the study cohort. Therefore, we analyzed the differences in AS events between tumor tissues and adjacent normal tissues in our study and performed prognostic analyses based on DEAS events.…”
Section: Discussionmentioning
confidence: 99%